Caetetermes taquarussu Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and new distributional records - Cuezzo, Carolina; Carrijo, Tiago F.; Cancello, Eliana M. (Zootaxa, 2015)
Caetetermes Fontes, 1981 is a monotypic South American genus of Nasutitermitinae. Its single species, Caetetermes taquarussu Fontes, 1981, was described based on morphological characters from soldiers and workers collected at three localities in the tropical rainforest of northeastern Ecuador. Several samples of C. taquarussu represented also by the imago caste were examined at the Museu de Zoologia da Universidade de São Paulo, São Paulo, Brazil (MZUSP) and the National Museum of Natural History, Washington D.C., USA (USNM). Herein, we describe the imago caste of Caetetermes for the first time, with notes on soldier and worker caste and new distributional records for the species.